Fundamentals of affinity cell separations. Issue 5 (25th October 2017) - Zhang, Ye; Lyons, Veronica; Pappas, Dimitri
Abstract: Cell separations using affinity methods continue to be an enabling science for a wide variety of applications. In this review, we discuss the fundamental aspects of affinity separation, including the competing forces for cell capture and elution, cell‐surface interactions, and models for cell adhesion. Factors affecting separation performance such as bond affinity, contact area, and temperature are presented. We also discuss and demonstrate the effects of nonspecific binding on separation performance. Metrics for evaluating cell separations are presented, along with methods of comparing separation techniques for cell isolation using affinity capture.